How should a theory of the firm incorporate advertising? - Lah, Marko (Teorija in praksa, 2011)
This article discusses the role of advertising expenses within the economic theory of the firm. In marketing and advertising textbooks advertising expenses are, from the perspective of the economic theory of the firm, viewed too narrowly. In contrast, standard economics textbooks start with the unrealistic perfect competition firm where advertising is not needed, while for the imperfect competition firm they extend the profit maximisation motive and concentrate on the optimisation of advertising expenses. The paper favours a more realistic, investment approach to advertising expenses which highlights problems such as the determination of advertising budgets in different firms in the network depending of their position, and the role marketing/advertising managers play within the chain of principal-agent relations in the firm. These topics are fundaments of the transaction cost theory of the firm which does not (sufficiently) explore advertising as an important tool for reducing transaction costs. The investment and transaction cost approach to the role of the firm's advertising are complementary.
Keywords: Advertising; Oglaševanje; Economic theories; Ekonomske teorije; Postkeynesianizem; Transakcijski stroški; podjetja; Postkeynesianism; Transaction costs